2014
DOI: 10.3390/toxins6123406
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of Ribosome-Associated Double-Stranded RNA-Dependent Protein Kinase (PKR) by Deoxynivalenol, Anisomycin and Ricin: A New Model for Ribotoxic Stress Response Induction

Abstract: Double-stranded RNA (dsRNA)-activated protein kinase (PKR) is a critical upstream mediator of the ribotoxic stress response (RSR) to the trichothecene deoxynivalenol (DON) and other translational inhibitors. Here, we employed HeLa cell lysates to: (1) characterize PKR’s interactions with the ribosome and ribosomal RNA (rRNA); (2) demonstrate cell-free activation of ribosomal-associated PKR and (3) integrate these findings in a unified model for RSR. Robust PKR-dependent RSR was initially confirmed in intact ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 53 publications
2
46
0
Order By: Relevance
“…Both PKR and Hck are associated with ribosomes and can sense trichothecene‐induced changes in ribosome structure. Zhou et al has revealed that various PKRs are basally connected with ribosome subunits and that DON‐induced PKR activation can be obtained in a cell‐free system (Lebrun et al, ; Zhou, He, Landgraf, Pan, & Pestka, ). In that model, PKR monomers are positioned to sense rRNA structure perturbations induced by DON or other ribotoxins.…”
Section: Deoxynivalenolmentioning
confidence: 99%
See 4 more Smart Citations
“…Both PKR and Hck are associated with ribosomes and can sense trichothecene‐induced changes in ribosome structure. Zhou et al has revealed that various PKRs are basally connected with ribosome subunits and that DON‐induced PKR activation can be obtained in a cell‐free system (Lebrun et al, ; Zhou, He, Landgraf, Pan, & Pestka, ). In that model, PKR monomers are positioned to sense rRNA structure perturbations induced by DON or other ribotoxins.…”
Section: Deoxynivalenolmentioning
confidence: 99%
“…In that model, PKR monomers are positioned to sense rRNA structure perturbations induced by DON or other ribotoxins. These rRNA structural changes could promote PKR dimerization and autophosphorylation (Lebrun et al, ; Zhou et al, ).…”
Section: Deoxynivalenolmentioning
confidence: 99%
See 3 more Smart Citations